Deciphering the dual-regulatory mechanism of Zn doping in spinel ZnCo₂O₄ for piezoelectric-activated peroxymonosulfate: Steering the high-valent cobalt-oxo pathway - Xiaoqing Lin; Zhen Tian; Jun Liang; Yizhe Shen; Shaojun Liu; Qunxing Huang; Xiaodong Li; Chen Sun (Water Research, 2026)

Depth-dependent source apportionment and health risk assessment of heavy metals in smelting soils via an integrated SOM-PMF modeling approach - Zulv Huang; Hanzhi Lin; Chao Chen; Jiaoliang Wang; Zhengfu Liu; Shaojun Jiang (Journal of Environmental Chemical Engineering, 2026)

An interlayer-engineered faradaic electrosorption system for co-removal of amikacin and heavy metal ions: Fe/Mo dual activation, energy storage, and adsorption selectivity - Pan Gong; Changhai Ji; Chang Liu; Xiaoshuang Yin; Wenzhong Yang; Lin Zhang; Shaojun Jiao; Feng Ge; Kegui Zhang (Chemical Engineering Journal, 2026)

Decoration of the ferritin nanocage surface to regulate the interfacial structure of emulsions for the development of a chitosan-based active film applied to Agaricus bisporus preservation - Kai Lin; Wenjie Zhao; Pengya Du; Suchen Zhao; Cailin Song; Yuanhao Guo; Jinling Cao; Yanfen Cheng; Feier Cheng; Wenfei Zhao; Cuiping Feng; Shaojun Yun (Food Hydrocolloids, 2026)

Robust CoNi-ZIF@PAN nanofiber membranes with prewetting-induced reversible wettability for switchable emulsion separation and catalytic dye degradation - Yiyi Lin; Huaqiang He; Thabang Mokoba; Hongyang Chen; Shaojun Yuan (Journal of Environmental Chemical Engineering, 2025)

Study on the strength and toxic leaching characteristics of CGF-solidified/stabilized ion-type rare earth tailings - Zhongqun Guo; Qiangqiang Liu; Shaojun Xie; Xi Cao; Xiaoming Lin; Zhaoming Huang (Science of The Total Environment, 2025)

Late Holocene extreme dust events in the arid Central Asia recorded by lake sediments in Tien Shan - Min Zheng; Xiaozhong Huang; Ning Wang; Menghan Qiu; Jun Zhang; Lixiong Xiang; Shaojun Chen; Muhammad Farqan; Ruiqi Min; Tao Wang; Chong Huang; Xiuxiu Ren; et al. (Quaternary Science Reviews, 2025)

Quantifying the contribution of different microenvironments to real-time PM2.5 exposure of rural and urban residents in southwest China - Pingshu Wang; Shaojun Lv; Nan Fu; Nan Lin; Ming Yang; Yunhang Jiang; Yuanchen Chen; Peng Zhang; Wei Du; Bo Pan (Building and Environment, 2025)

The formation of a hybrid fish derived from Labeo rohita ♀ × Cyprinus carpio ♂ and exhibiting stronger low temperature tolerance - Jiali Lin; Haoran Zhang; Jietao Wang; Bing Fu; Zexun Zhou; Wuhui Li; Huirong Yang; Shaojun Liu (Aquaculture, 2025)

Synergistic effect of dextran and ergosterol: A venue for fabricating a water-in-oil pickering emulsion gel as a solid fat substitute in cream cheese - Kai Lin; Pengya Du; Pengfei Dong; Yaxin Wang; Yuanhao Guo; Jinling Cao; Yanfen Cheng; Feier Cheng; Wenfei Zhao; Cuiping Feng; Shaojun Yun (Food Hydrocolloids, 2025)

The formation and growth characteristics of an all-female hybrid crucian carp - Lujiao Duan; ChaoLiang Shen; Jingjing Lin; Xiaoxia Xiong; Huan Sun; Ziyi Huang; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Potential mechanism of impaired perceptual reasoning in children with obstructive sleep apnea syndrome: topological analysis of brain white matter network employing graph theory - Weiting Tan; Shaojun Zhang; Xiaoyu Wang; Guisen Lin; Wenhong Ye; Hongwu Zeng (Brain Imaging and Behavior, 2025)

Textural properties prediction of KOH-activated carbon prepared from coal based on pyrolysis kinetics - Kai Wang; Guoxin Lin; Jun Meng; Jiangmin Guo; Bo Tan; Shaojun Liu; Qingyang Lin; Xuecheng Wu; Xiang Gao (Waste Disposal & Sustainable Energy, 2024)

Glycosylation of a ferritin nanocage with dextran as a novel emulsifier for the construction of dual-compartmental pickering emulsions to co-encapsulate hydrophobic bioactive compounds - Guo Yuanhao; Wang Yaxin; Dong Pengfei; Wang Shengnan; Lin Kai; Hou Jiangyan; Cui Fangming; Bi Shuyu; Cao Jinling; Cheng Yanfen; Cheng Feier; Yun Shaojun; et al. (Journal of Food Engineering, 2024)

Energy-economy-environment assessment of key feedstock production for ternary lithium-ion batteries via hydrometallurgical recycling and natural exploitation - Kai Wang; Quanshui Huang; Ran Feng; Shaojun Liu; Peng Xing; Zi-Tao Yu; Qingyang Lin; Xiang Gao (Journal of Cleaner Production, 2024)

Minimization of entropy generation rate in hydrogen iodide decomposition membrane reactor - Rui Kong; Lingen Chen; Shaojun Xia; Zhihui Xie; Yu Lin (Journal of Cleaner Production, 2024)

A novel method for MSWI fly ash resource based on calcium component regulation and CO2 mineralization - Jie Chen; Wanchen Zhu; Xiaoqing Lin; Xiaodong Li; Shaojun Liu; Jianhua Yan (Chemical Engineering Journal, 2024)

The key role of myostatin b in somatic growth in fishes derived from distant hybridization - Qingfeng Liu; Lujiao Duan; Bei Li; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Yuqin Shu; Fangzhou Hu; Jingjing Lin; Xiaoxia Xiong; Shaojun Liu (Science China Life Sciences, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Water-in-oil Pickering emulsion using ergosterol as an emulsifier solely - Yaxin Wang; Yuanhao Guo; Pengfei Dong; Kai Lin; Pengya Du; Jinling Cao; Yanfen Cheng; Feier Cheng; Shaojun Yun; Cuiping Feng (Food Research International, 2024)

Microbial α-L-arabinofuranosidases: diversity, properties, and biotechnological applications - Liangkun Long; Qunying Lin; Jing Wang; Shaojun Ding (World Journal of Microbiology and Biotechnology, 2024)

Effects of BC on metal uptake by crops (availability) and the vertical migration behavior in soil: A 3-year field experiments of crop rotation - Shaojun Jiang; Guangling Dai; Muhammad Saqib Rashid; Junhao Zhang; Hai Lin; Yuehong Shu (Chemosphere, 2024)

Comparative assessment of food safety regulations and standards for arsenic, cadmium, lead, mercury and iodine in macroalgae used as food and feed in China and Europe - Yingying Guo; Anne-Katrine Lundebye; Na Li; Åshild Ergon; Shaojun Pang; Yanhua Jiang; Wenjia Zhu; Yanfang Zhao; Xiaodong Li; Lin Yao; Lianzhu Wang; Inger Aakre (Trends in Food Science & Technology, 2023)

High-level production of cordycepin by the xylose-utilising Cordyceps militaris strain 147 in an optimised medium - Liangkun Long; Zhen Liu; Yizhou Wang; Qunying Lin; Shaojun Ding; Chuanhua Li; Chunying Deng (Bioresource Technology, 2023)

Synthesis of novel naphthalene-chimonanthine scaffolds hybrids with potent antibacterial or antifungal activity - Shaojun Zheng; Wenbin Wu; Qiaoju Jiang; Chuansong Lin; Yue Fang; Huihui Dai; Bing Tang; Yi Tan (Natural Product Research, 2023)

Synthesis and antifungal activity of novel chiral indole analogues - Yi Tan; Qiaoju Jiang; Chuansong Lin; Yue Fang; Huihui Dai; Bing Tang; Wenbin Wu; Shaojun Zheng (Natural Product Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Novel covalent organic frameworks based electrospun composite nanofiber membranes as pipette-tip strong anion exchange sorbent for determination of inorganic arsenic in rice - Binbin Kang; Haoliang Liu; Guoying Chen; Hetong Lin; Shaojun Chen; Tuanwei Chen (Food Chemistry, 2023)

Climate impacts of 2009/2010 mixed-type El Niño on double ITCZs over the eastern Pacific Ocean - Yinlan Chen; Li Yan; Jianjun Xu; Shaojun Zheng; Guihua Chen; Peixian Lin (Frontiers in Marine Science, 2023)
A double intertropical convergence zone (ITCZ) pattern emerges over the eastern Pacific Ocean in March-April. Their inter-annual variabilities may exert major climatic and ecological effects. El Niño-Southern Oscillation (ENSO) can significantly regulate the inter-annual variability of double ITCZs. ENSO diversity has increased in recent years. A mixed-type El Niño occurred in 2009/2010. Our results reveal that the meridional SSTA pattern in mixed-type El Niño is a combination of “SST warming with a maximum at the equator” (i.e., EP-type delta SST) and “north-warm and south-cold” (i.e., CP-type delta SST) patterns. In a mixed-type El Niño, both meridional EP-type and CP-type delta SST played a role and had corresponding climate impacts. Under the coordinated modulation of EP-type and CP-type delta SST in a mixed-type El Niño, the climate effect of EP-type delta SST (increasing equatorial precipitation) is weakened; while the climate effect of CP-type delta SST (enhancing the northern ITCZ and weakening the southern ITCZ) is amplified. The climate effect of mixed-type El Niño finally resembles that of typical CP-type El Niños, intensifying the north-south asymmetry of the eastern Pacific double ITCZs. This study will contribute to a better understanding of the impacts of ENSO diversity on double ITCZs in the eastern Pacific region.

RNA interference knockdown of insulin receptor inhibits ovarian development in Chilo suppressalis - Shuang Wu; Yan Tang; Shaojun Su; Wenbing Ding; Hualiang He; Jin Xue; Qiao Gao; Lin Qiu; Youzhi Li (Molecular Biology Reports, 2022)

Ar-plasma enhanced copper-nickel alloy catalysis for ammonia synthesis - Zhou Yimeng; Lv Jiabao; Peng Yaqi; Lin Xiaoqing; Lv Xingjie; Ye Qiulin; Liu Shaojun; Wu Angjian; Li Xiaodong (Waste Disposal & Sustainable Energy, 2022)

GW10, a member of P450 subfamily regulates grain size and grain number in rice - Penglin Zhan; Xin Wei; Zhili Xiao; Xiaoling Wang; Shuaipeng Ma; Shaojun Lin; Fangping Li; Suhong Bu; Zupei Liu; Haitao Zhu; Guifu Liu; Guiquan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Sodium P-aminosalicylic Acid Inhibits Manganese-Induced Neuroinflammation in BV2 Microglial Cells via NLRP3-CASP1 Inflammasome Pathway - Yuanyuan Fang; Dongjie Peng; Yuan Liang; Lili Lu; Junyan Li; Lin Zhao; Shiyan Ou; Shaojun Li; Michael Aschner; Yueming Jiang (Biological Trace Element Research, 2021)

Proteomic discovery of H2O2 response in roots and functional characterization of PutGLP gene from alkaligrass - Juanjuan Yu; Yongxue Zhang; Junming Liu; Lin Wang; Panpan Liu; Zepeng Yin; Siyi Guo; Jun Ma; Zhuang Lu; Tai Wang; Yimin She; Yuchen Miao; et al. (Planta, 2018)

Identification of Novel SCIRR69-Interacting Proteins During ER Stress Using SILAC-Immunoprecipitation Quantitative Proteomics Approach - Yujian Chen; Yong Liu; Shide Lin; Shuguang Yang; Haiping Que; Shaojun Liu (NeuroMolecular Medicine, 2017)

Manifold-Preserving Common Subspace Factorization for Feature Matching - Weidong Yan; ShaoJun Shi; Wei Lin; Lulu Pan; Jinhuan Wen (Journal of the Indian Society of Remote Sensing, 2016)

Identification and Expression Analysis of Genes Involved in Early Ovary Development in Diploid Gynogenetic Hybrids of Red Crucian Carp × Common Carp - Dong Liu; Shaojun Liu; Cuiping You; Lin Chen; Zhen Liu; Liangguo Liu; Jing Wang; Yun Liu (Marine Biotechnology, 2010)

Evidence for the Formation of the Male Gynogenetic Fish - Shaojun Liu; Qinbo Qin; Yuequn Wang; Hong Zhang; Rurong Zhao; Chun Zhang; Jing Wang; Wei Li; Lin Chen; Jun Xiao; Kaikun Luo; Min Tao; et al. (Marine Biotechnology, 2010)

Differential expression of Gnrh2, Gthβ, and Gthr genes in sterile triploids and fertile tetraploids - Yu Long; Min Tao; Shaojun Liu; Huan Zhong; Lin Chen; Suifei Tao; Yun Liu (Cell and Tissue Research, 2009)